2014
DOI: 10.1155/2014/543728
|View full text |Cite
|
Sign up to set email alerts
|

Degree and Rate of Growth Discordance in Dichorionic Twins Conceived by In Vitro Fertilization

Abstract: Objective. Our objective was to estimate degree and rate of discordant growth and its impact on perinatal outcome in dichorionic twin pregnancies conceived by in vitro fertilization (IVF) compared to those conceived spontaneously. Study Design. Growth discordance was defined as 90th percentiles for the study population. Adverse perinatal outcome was defined as 5-minute Apgar score <7 and/or admission to neonatal intensive care unit. Results. In the total study population of dichorionic twins (176 conceived by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The computation of the strength of association between BW discordance ≥30% and morbidity was affected by the inclusion of only two studies (2660 twins) (Figure ) . Overall, twins with BW discordance ≥30% were at higher risk of composite morbidity compared with controls (OR 3.4, 95% CI 2.2‐3.2; I 2 = 0%, P < 0.001) and this association persisted in DC (OR 3.6, 95% CI 2.3‐5.7; I 2 = 0%, P < 0.001) but not in MC ( P = 0.9) twins (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The computation of the strength of association between BW discordance ≥30% and morbidity was affected by the inclusion of only two studies (2660 twins) (Figure ) . Overall, twins with BW discordance ≥30% were at higher risk of composite morbidity compared with controls (OR 3.4, 95% CI 2.2‐3.2; I 2 = 0%, P < 0.001) and this association persisted in DC (OR 3.6, 95% CI 2.3‐5.7; I 2 = 0%, P < 0.001) but not in MC ( P = 0.9) twins (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 3594 articles were identified; of these, 208 were assessed with respect to their eligibility for inclusion (Supporting Information Appendices S1 and S2) and 25 studies were included in the systematic review ( Table 1, Supporting Information Table S1). [9][10][11][12][13][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Among them, 22 studies (including 11 470 twin pregnancies) reported the occurrence of morbidity in twins affected compared with those not affected by BW discordance, and three exclusively reported on the occurrence of morbidity in the smaller compared with larger twin. 30,32,39 The prevalence of ≥15%, 20%, 25% and 30% BW discordance was 25 14.5% (95% CI 11.5-18.5) and 2.8% (95% CI 0.9-6.4).…”
Section: General Characteristicsmentioning
confidence: 99%
“…1,[9][10][11][12][13][14] A majority of studies reported that ART twin pregnancies had obstetric outcomes comparable to SC twin pregnancies. 1,9,10,[14][15][16][17][18] Several studies found higher risks of adverse perinatal outcomes among ART-related twin pregnancies, [19][20][21][22] whereas others reported reduced adverse outcomes among iatrogenic twin pregnancies. 12,23 Therefore, it is not yet clear whether ART-related twins have higher risks than spontaneous conceived twins and of what magnitude these risks are.…”
Section: Introductionmentioning
confidence: 99%
“…Although some reports find poorer outcomes among those singletons resulting from infertility treatments compared with spontaneously conceived (SC) ones, 6‐8 findings among twin gestations are inconsistent 1,9‐14 . A majority of studies reported that ART twin pregnancies had obstetric outcomes comparable to SC twin pregnancies 1,9,10,14‐18 . Several studies found higher risks of adverse perinatal outcomes among ART‐related twin pregnancies, 19‐22 whereas others reported reduced adverse outcomes among iatrogenic twin pregnancies 12,23 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies may misrepresent the infertile population, and the conclusions may be less generalizable. In addition, conflicting results may be from studies only adjusting for some confounding variables or none at all [9,10,22,23].…”
Section: Introductionmentioning
confidence: 99%